(untitled) (Journal of Ideas in Health, 2023)
Background: The case we are reporting is about one of the rare manifestations of severe combined immunodeficiency, Omenn syndrome (OS). Case presentation: A 43-days-old female presented with thick diffuse erythrodermic scaly ichthyosiform lesions on the scalp, face, and trunk since birth. lymphadenopathy, splenomegaly, and growth retardation as well as eosinophilia and increased serum IgE levels. A pregnancy was planned for an allograft of bone marrow, but the procedure was not carried out due to a persistent post-covid pneumopathy with bilateral parenchymal condensation that resulted in death. Conclusion: This case report intends to incite clinicians to be alert to this possible diagnosis and not to underrate an immune deficiency in the case of neonatal erythroderma.